71.3k views
4 votes
Solve for u.
-3= -1/u+1

User Steve Baek
by
5.7k points

2 Answers

5 votes

Answer:

-2/3

Explanation:

multiply each side by u +1 to get it out of the denominator

-3(u + 1) = -1

now use distributive property

-3u - 3 = -1

add the 3 to move it over

-3u = 2

now divide by -3

u = -2/3

User Pavan Kumar V
by
4.5k points
1 vote

Answer:

u = -2/3

Explanation:

-3 = -1/ (u+1)

Multiply each side by (u+1)

-3 *(u+1) = -1/ (u+1) * (u+1)

-3 (u+1) = -1

Distribute

-3u -3 = -1

Add 3 to each side

-3u -3+3 = -1+3

-3u = 2

Divide each side by -3

-3u/-3 = 2/-3

u = -2/3

User Lassi
by
3.9k points